Efektivitas Kinerja Pegawai dalam Meningkatkan Kualitas Pelayanan Publik - Salman Alfarizi Muhtar; Hayat; Septina Dwi Rahmawati (Program Study Office Adminstrative of Akademi Komunitas Teknologi Syarifuddin Lumajang, 2025)
The purpose of this study is to ascertain how well employee performance contributes to raising the standard of public services. The study model generated descriptive data in the form of people's written or spoken words and observed behavior by using qualitative research methodologies to investigate and comprehend the meanings that individuals or groups of people perceive regarding social or humanitarian concerns. The study was carried out in North Maluku Province, as this area is among the eastern Indonesian cities with a low growth rate of MSMEs, where many cooperatives are notactively shocked to say that they are not functioning as anticipated, Socio Economic Research and Development and there-remains expected to enhance economic growth and MSMEs. The researcher employed a purposive sampling technique that is non-random and does not rely on reference data sources for data collection. This is grounded in the researcher's aim to comprehend the matter at hand concerning how well employees perform at the Cooperatives and Small and Medium Enterprises (MSMEs) Office of North Maluku Province via individuals whom the researcher deems to possess pertinent knowledge and expertise.